Digitalisasi Lagu Anak sebagai Media Ekspresi Emosi Anak Usia Dini - Novita Qori; Anita Afrianingsih (Universitas Islam Lamongan, 2025)
This study examines how the digitalization of children’s songs in early childhood education functions as a medium for children’s emotional expression. The study is grounded in the importance of emotional development from an early age and the increasing integration of digital media in early childhood learning contexts. A qualitative approach with a case study design was employed. The units of analysis included young children, teachers, and parents at RA Al Ma’arif Bandungharjo, Donorojo District, Jepara Regency. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data display, and thematic conclusion drawing. The findings indicate that digitally formatted children’s songs facilitate emotional expression both verbally and nonverbally. Songs with cheerful rhythms encourage the expression of positive emotions such as joy and enthusiasm, while songs with slower tempos help children calm themselves and alleviate negative emotions. The integration of digital media also provides multisensory stimulation that enhances children’s emotional responses. The study concludes that the digitalization of children’s songs serves not only as entertainment but also as a supportive tool for emotional expression and the early development of emotional regulation in young children. These findings contribute to the literature on digital media and early childhood emotional development and offer practical recommendations for teachers and parents to use digital songs purposefully as learning strategies that are responsive to children’s emotional needs.